Política educacional e ações universitárias: um estudo sobre os cursos seqüenciais - Zapparoli, Irene Domenes (2007)
The proposal of sequential courses by the Law of Guidelines and Bases of the National Education (LDB), number 9.394/96, provoked alterations in the educational field, specifically regarding the assimilation of the agents involved with the Brazilian higher education. These courses are considered as a modality of higher education whose agents involved are the government, the higher education, representative organs of class, and all the university community. This work is directed by the issue of the creation, implantation and implementation of such courses in the Brazilian higher education. The objectives of mapping the legislation, the conformation and the operation of the sequential courses were unfolded from this concern. So, a documental study was put into practice, between 2004 and 2006, bringing 762 documents, including the wide legislation with all the sequence of the general order, as well as the documents from two universities in order to be analyzed about the particular reactions concerning such prescriptions and legal possibilities. The study also presents the analyses of some passages taking into account Bourdieu s concept of educational field, in order to apprehend and understand objects of disputes. Some results may be elicited synthetically: a) through the legislation there is an imperceptible relationship among job market, sequential courses and representative organs of class; b) the educational legislation is interpreted differently in the university reality in its social role; c) the universities under more detailed study act in a different way internally, one of them debating the theme but not the other; d) the relationship between universities and society is different, but it has to be considered that the institution that accepted the sequential courses presented itself more willing to open possibilities, although it had unleashed the process without debating it. The development of the study allowed us to detect different elements that ordered the creation of the courses and their implementation. The legislation analyzed in its text and also in the arguments of its proposition and occurrences allowed us a gradual detection about what is underneath: the diversity and complexity of current life; the interference of models historically constituted in the international scope; the necessity of considering the priorities of the World Bank and enlargement of the market logic in the higher education, mainly because of the higher percentage of private institutions that implemented the sequential courses; the necessity of maintaining, by the disproportional education, the social differences not only in the primary and secondary schools but also in the higher education. The institutions are not passive; the agents move in face of the possibilities characterizing forms of university organization that match different models